2019
DOI: 10.1111/dar.12886
|View full text |Cite
|
Sign up to set email alerts
|

Did New Zealand’s new alcohol legislation achieve its object of facilitating public input? Qualitative study of Māori communities

Abstract: Background and Aims. The Treaty of Waitangi stipulates equality between M aori and non-M aori, yet M aori continue to have substantially poorer health, a driver of which is alcohol-related morbidity. In 2012, the New Zealand government introduced legislation claiming it would facilitate community input on decisions about alcohol. We investigated the experience of M aori communities with the new law. Design and Methods. We obtained submissions made to local governments and invited a diverse range of submitters … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…Searches of other sources identified one report and one thesis for inclusion, equating to a total of eight studies eligible for inclusion (Table 1). Only one study specifically documented Māori engagement with alcohol interventions (Kypri et al, 2019). The remaining studies examined Māori perspectives on alcohol or alcohol-related harm (Herbert et al, 2018a(Herbert et al, , 2018bHutton & Wright, 2015;Lyons et al, 2014;J.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Searches of other sources identified one report and one thesis for inclusion, equating to a total of eight studies eligible for inclusion (Table 1). Only one study specifically documented Māori engagement with alcohol interventions (Kypri et al, 2019). The remaining studies examined Māori perspectives on alcohol or alcohol-related harm (Herbert et al, 2018a(Herbert et al, , 2018bHutton & Wright, 2015;Lyons et al, 2014;J.…”
Section: Resultsmentioning
confidence: 99%
“…Only one study examined Māori perspectives on interventions. In this study the authors reported that Māori were interested in involvement with decisions on alcohol policy changes, and that local councils should alter their communication methods to better facilitate the involvement of Māori (Kypri et al, 2019).…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations